Couples’ decision-making on post-partum family planning and antenatal counselling in Uganda: A qualitative study - Willcox, Merlin L.; Mubangizi, Vincent; Natukunda, Silvia; Owokuhaisa, Judith; Nahabwe, Haeven; Nakaggwa, Florence; Laughton, Matthew; Chambers, Isabella; Coates, Sabine; King, Emma; Fall, Emma; Muller, Ingrid; et al. (PLoS ONE, 2021)
Background: Although health workers have been trained to provide post-partum family planning (PPFP), uptake remains low in Uganda. An important reason is that women want the agreement of their partner, who is often absent at the time of delivery. In order to address this, we aimed to understand the views of couples and explore barriers and facilitators to implementation of antenatal couples’ counselling on PPFP in Uganda. Methods: We conducted individual interviews with a purposive sample of 12 postpartum and 3 antenatal couples; and 34 focus groups with a total of 323 participants (68 adolescent women, 83 women aged 20–49, 79 men, 93 health workers) in four contrasting communities (urban and rural) in South-West and Central Uganda. These were recorded, transcribed, translated, and analyzed thematically. Results: Although most participants felt that it is important for partners to discuss family planning, half of the couples were unaware of each other’s views on contraception. Most had similar views on motivation to use family planning but not on preferred contraceptive methods. Most liked the idea of antenatal couples’ counselling on PPFP. The main barrier was the reluctance of men to attend antenatal clinics (ANC) in health facilities. Respondents felt that Village Health Teams (VHTs) could provide initial counselling on PPFP in couples’ homes (with telephone support from health workers, if needed) and encourage men to attend ANC. Suggested facilitators for men to attend ANC included health workers being more welcoming, holding ANC clinics at weekends and “outreach” clinics (in rural villages far from health facilities). Conclusion: Antenatal couples’ counselling has the potential to facilitate agreement PPFP, but some men are reluctant to attend antenatal clinics. Counselling at home by VHTs as well as simple changes to the organization of antenatal clinics, could make it possible to deliver antenatal couples’ counselling on PPFP.
Keywords: Couples’ decision-making; Family planning services; Antenatal counselling; Uganda